2006
DOI: 10.1007/s10832-006-7775-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strontium gallate additions on sintering behavior of gadolinia-doped ceria

Abstract: The densification behavior and grain growth of Ce 0.8 Gd 0.2 O 1.9 ceramics were investigated with the strontium gallate concentration ranging from 0 to 5 mol%. Both the sintered density and grain size were found to increase rapidly up to 0.5 mol% Sr 2 Ga 2 O 5 , and then to decrease with further addition. Dense Ce 0.8 Gd 0.2 O 1.9 ceramics with 97% of the theoretical density could be obtained for 0.5 mol% Sr 2 Ga 2 O 5 -added specimen sintered at 1250 • C for 5 h, whereas pure Ce 0.8 Gd 0.2 O 1.9 ceramics nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Adding a small amount of Sr to doped-ceria has been proved very effective in reducing the sintering temperature of ceria. [37][38][39] It should be noted here that the densification observed in this experiment is not as pronounced as that observed when the SDC is in contact with the LSCF cathode for only 2 hours at 1200 • C. This could be due to the larger gas phase diffusion distance or higher potential for loss of gas phase species to the surrounding atmosphere.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Adding a small amount of Sr to doped-ceria has been proved very effective in reducing the sintering temperature of ceria. [37][38][39] It should be noted here that the densification observed in this experiment is not as pronounced as that observed when the SDC is in contact with the LSCF cathode for only 2 hours at 1200 • C. This could be due to the larger gas phase diffusion distance or higher potential for loss of gas phase species to the surrounding atmosphere.…”
Section: Resultsmentioning
confidence: 58%
“…[37][38][39] It should be noted here that the densification observed in this experiment is not as pronounced as that observed when the SDC is in contact with the LSCF cathode for only 2 hours at 1200…”
mentioning
confidence: 52%
“…23,24 It is also reported that small addition of Sr 2 Ga 2 O 5 considerably improved sinterability of Gd-doped CeO 2 . 25 In this study, Sr-substituted LLZ-Ga, Li 6.25+x Ga 0.25 La 3-x Sr x Zr 2 O 12 (LLZ-GaSr), was synthesized to improve sinterability and ionic conductivity of LLZ-Ga. The relationship between composition, structure, sinterability and ionic conductivity of LLZ-GaSr is discussed.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Most of the investigators have studied the preparation of ultra fine ceria-based ceramic powders by chemical routes such as coprecipitation and sol-gel process. Recently, it has been reported that Ga 2 O 3 , [10][11][12] Al 2 O 3 , [13,14] MnO 2 , [15] Fe 2 O 3 , [16] Co 3 O 4 , [17] CoO, [18] and Sr 2 Ga 2 O 5 [19,20] are effective sintering aids for the densification of ceria-based ceramics.…”
Section: Introductionmentioning
confidence: 99%